Factors related to neonatal asphyxia at Adjidarmo Hospital Rangkasbitung Lebak Banten - Shinta Novelia; Yenny Aulya; Syifa Aulia Rahmawati (Program Studi Ilmu Keperawata Fakultas Kedokteran Universitas Malahayati Bandar Lampung, 2021)
Background: According to who the infant mortality rate in Indonesia ranks fourth highest. The highest contributor to neonatal mortality is 335 per 1,000 live births. One of the complications of Neonatal death is due to Asphyxia.Purpose: To determine the factors associated with the occurrence of asphyxia neonatorum at Dr. Adjidarmo HospitalMethod: An analytical survey research design with cash control approach. The sample in this study is 119 case respondents (asphyxia) and 119 (without asphyxia). The sampling technique is simple random sampling. The instrument is a medical record which records the secondary data. Results: Univariate analysis found that 149 respondents (62.6%) does not face Premature Rupture of Membrane (PROM), 172 infants are not low birth weight (72.3%), 174 respondents (73.1%) are not prolong labour an delivery 192 infants (80.7 %) are not premature, 134 respondents are (56.3%) not preeclampsia, 126 respondents (52.9%) are Cesarean Section women, and 185 respondents (77.7%) are not anemic. The results of the chi-square test showed that all independent variables had a relationship with the incidence of neonatal examination including premature rupture of membranes (p = 0.011), LBW (p = 0.000), prolonged birth (p = 0.009), preeclampsia (p = 0.037), type of birth (p = 0.009), premature (p = 0.001), and anemia (p = 0.019).Conclusion: There is a relationship between PROM, LBW, prematurity, prolonged birth, preeclampsia, type of delivery, and anemia with the incidence of neonatal asphyxia. It is recommended that pregnant women carry out pregnancy screening and routine ANC to detect early possible neonatal asphyxia.